2016
DOI: 10.1186/s10194-016-0623-z
|View full text |Cite
|
Sign up to set email alerts
|

Plasma urotensin-2 level and Thr21Met but not Ser89Asn polymorphisms of the urotensin-2 gene are associated with migraines

Abstract: BackgroundUrotensin-II (U-II) is a peptide recognized by its potent vasoconstrictor activity in many vascular events, however the role of urotensin-II in migraine has not been considered yet. The molecular mechanisms and genetics of migraine have not been fully clarified yet, but it is well-known that vascular changes considerably contribute in pathophysiology of migraine and also its complications. The aim of this study was to analyze the plasma U-II levels along with genotype distributions and allele frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 39 publications
2
12
2
Order By: Relevance
“…Our results indicate that the common genetic variation in the UTS2 gene unlikely plays a role in the development of migraine. However, these results are not in agreement with the findings reported by Geyik et al [13] who found that Thr21Met polymorphism was associated with the risk for migraine. Several factors could have contributed to the disparate results.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Our results indicate that the common genetic variation in the UTS2 gene unlikely plays a role in the development of migraine. However, these results are not in agreement with the findings reported by Geyik et al [13] who found that Thr21Met polymorphism was associated with the risk for migraine. Several factors could have contributed to the disparate results.…”
Section: Discussioncontrasting
confidence: 99%
“…Several factors could have contributed to the disparate results. First, although their study was conducted at the same university as ours, Geyik et al [13] did not specifically indicate the ethnic background of their study population. In our study, all participants were Caucasians and of Turkish origin.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Lipid peroxides are oxidation products and thus a biomarker of oxidative stress . The reason for higher levels interictally in migraineurs is unclear but may reflect lower activity of certain antioxidant enzymes, and/or increased activity of oxidant‐generating vasoconstrictors such as angiotensin, endothelin‐1, or urotensin‐2 . Alternatively, the source may be cortical hyperexcitablity, perhaps resulting in excessive oxidant production as a byproduct of the high metabolic rate .…”
Section: Migraines and Oxidative Stressmentioning
confidence: 99%